A toponímia de São Tomé e Príncipe - Balduino, Amanda Macedo; Araujo, Gabriel Antunes de; Agostinho, Ana Lívia (Acta Scientiarum. Language and Culture, 2021)
gabrielaraujo@um.edu.mo ABSTRACT. This study describes the toponymic profile of the Democratic Republic of São Tomé and Príncipe (STP), a former Portuguese colony. Here, we consider (i) its linguistic contact situation, reflected in the toponyms of non-Portuguese etyma (mainly from national languages), and (ii) the structure of the toponymic syntagma in Portuguese. Toponyms are created according to a place’s geographic, social, historical, and linguistic reality. Therefore, STP’s toponyms are the locus of the Santomean linguistic ecology and memory. Due to its linguistic diversity, the study of Santomean toponymy is transdisciplinary. It contributes to understanding different languages that share São Tomé and Príncipe’s ethnicity and linguistic heritage, including multilingual synchronic and/or diachronic conjunctures and the political importance of Portuguese. STP’s toponymy expresses a multilingual conjuncture common to the country since the arrival of the Portuguese and (mainly) enslaved Africans from different regions of Africa. Although the Portuguese language and culture have influenced most local toponymy, the Santomean toponymic profile contains endemic linguistic and cultural specificities. Thus, natural phenomena, along with political and historical events, among others, play a role in forming toponyms and characterizing the local toponymy as unique.